Green Entrepreneurship: Literature Review and Agenda for Future Research - Muo Ik; Azeez A. Adebayo (International Journal of Entrepreneurial Knowledge, 2019)
Advocacy for pro-environmental behaviour in the business arena is on the increase. Yet, many businesses have continued to indulge in “business-as-usual” practices, which are preoccupied with profit maximization objectives at the expense of all other social benefits. Such anti-environment practice has little or no regard for flora and fauna wellbeing. Hence, the main objective of this study is to review, explore and synthesize current views in the field in view of clarifying relevant concepts in green entrepreneurship context. Also, to identify behavioural and performance standards required of green entrepreneurship growth and development. To achieve the study objectives, we adopted integrative review of literature methodology. Concerning the findings, the paper identified new trends in green entrepreneurship and identified the need to clarify some relevant concepts, such as: industry life cycle, entrepreneurship knowledge sharing, institutional framework, entrepreneurship financing, green entrepreneurship decision-making process among others. We also identified the need to properly delineate the process leading to the practice of green entrepreneurship as a departure from the old entrepreneurship philosophy. Therefore, we recommend that further studies should endeavour to focus on identifying the step-by-step processes involved in the green entrepreneurship practice for the possibility of wider accessibility and ease of understanding of prospective green entrepreneurs in the interest of green entrepreneurship growth and development. Finally, we identified the dearth of literature with change management scholars’ view and contributions to the emancipation of green entrepreneurship from the cocoon of traditional entrepreneurship management practice hence, we threw it open for future research undertaking.